2017
DOI: 10.1016/j.jallcom.2017.04.111
|View full text |Cite
|
Sign up to set email alerts
|

Lattice distortion induced site dependent carbon gettering at twin boundaries in silicon

Abstract: The interactions between substitutional carbon atoms and Σ3 {111}, Σ9 {221}, and Σ27 {552} twin boundaries (TB) in silicon were investigated by first-principles calculations. The preferential segregation sites and segregation energy for carbon at different TBs were determined. It shows that segregation of carbon atoms at Σ3 {111} TB is energetically unfavorable while Σ9 {221} and Σ27 {552} TBs are efficient gettering centers for carbon. A linear relationship between the atomic-site specific segregation energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…{112} GB. This behavior is analogous to the C segregation in Σ27 {552} TB in Si, as studied in a previous work [23], in which the joint site of five-fold and two six-fold rings was predicted to be the most attractive for C segregation. The utmost positive γ seg , i.e.…”
Section: Carbon Segregation At σ3 {112} Gbssupporting
confidence: 78%
See 2 more Smart Citations
“…{112} GB. This behavior is analogous to the C segregation in Σ27 {552} TB in Si, as studied in a previous work [23], in which the joint site of five-fold and two six-fold rings was predicted to be the most attractive for C segregation. The utmost positive γ seg , i.e.…”
Section: Carbon Segregation At σ3 {112} Gbssupporting
confidence: 78%
“…In a previous work [23], it was revealed that the intrinsic lattice distortion (mainly bond length deviation) in the TBs in mc-Si is the main driving force for the C gettering, where core sites with a smaller ABL in the TBs exhibit a higher propensity for C segregation. A linear correlation was demonstrated between the atomic-site specific segregation energy for C at TBs and the ABL of atomic sites [23]. An attempt is also made to correlate the segregation energy of C and the geometrical character of the segregation sites (including ABL, bond angle, etc.)…”
Section: Carbon Segregation At σ3 {112} Gbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the detection limit of 0.01 at.% expected for GB segregation in our experiments [40], Γ As would increases superlinearly with increasing γ GB . The segregation characteristic for As dopants is, therefore, different from that for neutral impurity atoms such as oxygen [36,52] and carbon [53,54], in which the number of segregating atoms would exhibits a linear correlation with γ GB via elastic interactions [36] .…”
Section: Segregation Abilities Depending On Gb Structuresmentioning
confidence: 95%
“…Furthermore, density-functional theory (DFT) calculations show the S-3 GB to favor interstitial Fe [11] as well as P and As substitutional [10] segregation. Both {112} boundaries also show very different site selectivity for C substitutionals [12].…”
Section: Introductionmentioning
confidence: 99%